Khitanan on Pontianak Malay Society West Kalimantan - Dwi Pratiwi, Sella (The Pontianak State Institute of Islamic Studies, 2018)
Indonesia has a wide variety of ethnic groups, customs and cultures. One of the interesting cultures is the culture of Khitanan (circumcision) of Pontianak Malay society, West Kalimantan. This article will describe Khitanan culture in Pontianak Malay society to describe the diversity of national culture. Data obtained through interviews and observations in Pontianak. Shows that Khitanan is practiced for baby girls and boys. Khitanan or circumcision is the Islamic Shari'a which becomes sunnah of Prophet Mohammed. Become a requirement for one's perfection in worshiping Allah SWT. For a baby girl it is usually done when the baby is new baby born or at 40 days old by a midwife. For boys they will be circumcised when the age of 8 to 12 years and it is carried out by a mantri (traditional doctor) or doctor. Before boys are circumcised, there are several processions that must be carried out first. Circumcised children also face taboos that should not be violated. After the boy was circumcised, besanji was carried out and the recitation of selamat prayer had been given fluency in carrying out the Shari'a required by religion. The host invites neighbors and families. The food provided is the same at the marriage reception; the difference is when a marriage reception arrange on the tables but in Khitanan event, the food will be arranged on the carpets. Besanji ended the traditional procession of Khitanan culture in Pontianak. This description shows that Pontianak Malay tribe considered Khitanan is important. The procession and series also show differences with Khitanan culture in other regions.